Novel methods for micellar electro kinetic chromatography and preconcentration on traditional micro fluidic devices and the fabrication and characterization of paper micro fluidic - Hoeman, Kurt W. (Kansas State University, 2010)
Chemical separations are a necessary component in many scientific analyses. Microfluidics, the use of micron-sized fluidic channels defined in glass or polymer blends, is a powerful branch of separation science that is developing rapidly. Miniaturized analytical devices offer important advantages compared to traditional bench-top techniques, most notably capillary electrophoresis (CE). This dissertation was focused on developing several novel methods to improve microfluidic based separations and techniques. The electrophoretic separation of small similarly charged analytes can be very difficult. Chapter 2 discusses a new buffer that has been developed for fast, high efficiency separations of amino acids by micellar electrokinetic chromatography (MEKC). This buffer is more environmentally friendly than the most commonly used surfactant containing buffers for MEKC separations. It uses a commercially available dish washing soap by Seventh Generation™ Inc. that contains three micelle forming agents; sodium lauryl ether sulfate (anionic), cocamidopropyl betaine (zwitterionic), and cocamide monoethanolamine (MEA) (non-ionic), and is completely void of organic solvents. Many biological samples contain analytes below the limit of detection of traditional detection systems; therefore, chapter 3 reports the fabrication of nanoporous membranes on microfluidic devices that are capable of analyte concentration enrichment. Donnan exclusion is responsible for the preconcentration of fluorescent dyes near a charged, porous titania membrane. The level of analyte enrichment was monitored, and enrichment factors greater than 4000 in 400 s were obtained for 2,7-Dichlorofluorescein. Chapter 4 describes the fabrication and characterization of paper based microfluidic devices. Mixtures of acrylate modified photocurable polymers were used to photolithographically define channels on multiple paper substrates. Flow characteristics are described and their use for monitoring complications associated with type 1 diabetes is demonstrated. Finally in Chapter 5, Sol-gel modified gold surfaces for preventing protein adsorption during surface plasmon resonance (SPR) detection are also presented.
Keywords: Microfluidics; Analyte preconcentration; Micellar electokinetic chromatography; Chemistry, Analytical (0486)